Segmentation of Bottled Water Consumers in Poland - Joanna M. DZIADKOWIEC; Urszula BALON (Communications of International Proceedings, 2021)
The bottle water market was estimated at 437 billion liters in 2017 and is expected to reach 623 billion liters in 2021, growing at a CAGR of 92,7% during 2017-2021. The dynamic development of this market is also observed in Poland, the consumption of bottled water in Poland is constantly growing, in 2019 it was 114 liters per capita, approaching the European average. However, despite the significant increase, Poles still consume much less bottled water than, for example, Italians or Germans. Therefore, it can be concluded that, on the one hand, the purchasing habits on the Polish bottled water market have developed, and on the other hand, there is still a development potential of this market. This article reviews the factors that motivate the purchase and consumption of bottled water. The goal of this research is to identify emerging patterns of purchasing and consumption of bottled water in Poland. The study was conducted with a group of 742 respondents representing from 2 districts in southern Poland, CAWI and CAPI  method were used to collect data. Next cluster analyzes were performed to determine whether different patterns of buying and consuming bottled water coexist. Two methods were used for the clustering procedure - Ward's method (squared Euclidean distance) and k-means solution. A three-cluster (three distinct groups of respondents ) solution provided the best results. Ss a result, three different groups of respondents (segments) were identified: 1) taste sensitive, 2) healthy lifestyles, 3) careless consumers.
Keywords: Segmentation; Bottled Water; Consumer Behavior